A 32-year-old man with plexiform schwannoma of the thyroid gland: a case report - Il Rae Park; Min Chong Kim; Seung Min Chung; Si Youn Song (Journal of Yeungnam Medical Science, 2024)
Plexiform schwannomas representing a rare subset, comprise 5% of all schwannomas. However, their occurrence in the thyroid gland is exceptionally rare. A 32-year-old male presented with an incidentally discovered, asymptomatic thyroid mass. Imaging revealed an approximately 5 cm heterogeneous solid mass on the right thyroid lobe extending to the upper mediastinum and directly invading the upper trachea. Under the suspicion of thyroid malignancy, the patient underwent right thyroidectomy. Histological examination confirmed a plexiform schwannoma with S100-positive spindle cells. Currently, the patient is undergoing outpatient follow-up, with no reported complications. To our knowledge, this is the first documented case of plexiform schwannoma of the thyroid gland within the English literature. This case highlights the diverse and unpredictable clinical manifestations of thyroid masses, emphasizing the importance of a multidisciplinary approach for diagnosing and managing rare entities, such as thyroid gland schwannomas.